Multi-disciplinary shape optimization of notches in 2-D machine components - Wilczyński, Bogdan (Computer Assisted Methods in Engineering and Science, 2023)
A multi-disciplinary, numerical approach to shape optimization of notches is presented. The design of the optimal shape of notches in 2-D elastic machine (structural) components is formulated using the Fictitious Stress Method. The design objective is to minimize the maximum effective stress for a given load. Formulation is based on constant stress boundary element. A special concept of segmented Bezier interpolants is adopted for defining geometry of the machine component, and the Sequential Linear Programming is used as optimization procedure.